The blood / 3. - MacHale, D. J. (Morpheus Road, 2012)
"A final showdown is in order between best friends Marshall and Cooper and the terrifying villain Damon, who's more determined than ever to break down the walls between the worlds of the living and the dead. Marshall is forced to make a brave and shocking choice when the battle is on the line, and he and Cooper might be rewarded with help from someone quite unexpected"--Provided by publisher.